Potensi Tabha Lame sebagai Pangan Fungsional Tradisional untuk Mendukung Laktasi: Kajian Etnobotani di Suku Ua Kabupaten Nagekeo - Wae, Veronika P. Sinta Mbia; Babo, Anjelina Larici; Owa, Maria Fransiska; Bupu, Yuliana; Ngange, Bonefasia Gabriela Noni; Owa, Maria Prima (Biocaster : Jurnal Kajian Biologi, 2025)
Tabha Lame is a traditional food of the Ua Tribe in Nagekeo Regency which has been traditionally believed to increase breast milk production. However, this belief has never been scientifically studied and systematically documented, especially regarding its nutritional function and ethnobotanical value. This study aims to identify the composition of ingredients, processing, and nutritional potential of Tabha Lame as a locally based functional food. This study was conducted using a qualitative descriptive approach through interviews and field documentation methods with traditional leaders and women who possess traditional knowledge. The results show that Tabha Lame is made from local ingredients, such as: jali (Coix lacryma-jobi), moringa leaves (Moringa oleifera), peanuts (Arachis hypogaea), and coconut milk cooked using the Dhedhu Zaka technique. The content of phytoestrogens, iron, vegetable protein, vitamin A, and unsaturated fatty acids in these ingredients contribute to supporting the lactation process. The slow cooking process maintains micronutrients, while the symbolic presentation demonstrates the integration between nutrition and culture. The conclusion of this study confirms that Tabha Lame is a locally based functional food with potential for development in community-based nutritional interventions for breastfeeding mothers and the preservation of traditional knowledge.